POLITENESS AND INFORMATION QUESTIONING STYLES OF CASHIERS AMONG SELECTED FAST-FOOD CHAINS - Sophia Colynn D. Cinco; Jillian Monikah A. Tatad; Rowanne Marie Ramos Maxilom (Universitas Muhammadiyah Surakarta, 2019)
This study identified the views of politeness and information questioning style of the interaction between the cashiers and their customers. By recording the interactions between the cashiers and customers, the results revealed that the predominant level of politeness was “Don’t impose” while direct order was the frequently used information questioning style. Males were found to be more polite because they frequently used compound request than female cashiers. Hence, this study showed evidence that male crew members were more polite compared to female counterparts.